2017
DOI: 10.1016/j.tips.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptors in Myelinating Glia

Abstract: The G protein-coupled receptor (GPCR) super-family represents the largest class of functionally selective drug targets for disease modulation and therapy. GPCRs have been studied in great detail in central nervous system (CNS) neurons, yet these important molecules have been relatively understudied in glia. In recent years, however, exciting new roles for GPCRs in glial cell biology have emerged. Here, we focus on key roles for GPCRs in a specialized subset of glia, myelinating glia. We highlight recent work f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The G-protein coupled receptor GPR126 in Schwann cells is essential for both developmental myelination and re-myelination (Mogha, D'Rozario, & Monk, 2016;Mogha, Harty, et al, 2016). This protein is not required for the maintenance of myelin in uninjured nerves, but inactivation of Gpr126 in repair Schwann cells results in reduced axonal regeneration, reduced expression of TNF and a restricted group of chemokines, and impaired recruitment of macrophages, cells which potentially promote axonal regeneration (Barrette et al, 2008).…”
Section: Schwann Cells Elevate Expression Of Both Erbb2/3 Receptors Andmentioning
confidence: 99%
“…The G-protein coupled receptor GPR126 in Schwann cells is essential for both developmental myelination and re-myelination (Mogha, D'Rozario, & Monk, 2016;Mogha, Harty, et al, 2016). This protein is not required for the maintenance of myelin in uninjured nerves, but inactivation of Gpr126 in repair Schwann cells results in reduced axonal regeneration, reduced expression of TNF and a restricted group of chemokines, and impaired recruitment of macrophages, cells which potentially promote axonal regeneration (Barrette et al, 2008).…”
Section: Schwann Cells Elevate Expression Of Both Erbb2/3 Receptors Andmentioning
confidence: 99%
“…Several GPCRs are now known to regulate myelinating glial cell development (Mogha, D'Rozario, & Monk, ). For example, GPR37 was recently identified as a potent negative regulator of oligodendrocyte differentiation and myelination.…”
Section: Hypothesis‐driven Approaches and Identification Of Strategiementioning
confidence: 99%
“…Available evidence has suggested that Schwann cells (SC) require signaling from the cAMP to initiate the myelination program. This idea is supported by studies on isolated SC showing as prolonged cAMP stimulation increases the expression of proteins and lipids specific to the myelinating SC phenotype . In addition, different works showed that elevation of cAMP levels in SC is dependent by GPR126 protein, a highly conserved orphan G protein‐coupled receptor, critical for myelination within the peripheral nervous system (PNS) during development .…”
Section: Discussionmentioning
confidence: 91%
“…This idea is supported by studies on isolated SC showing as prolonged cAMP stimulation increases the expression of proteins and lipids specific to the myelinating SC phenotype . In addition, different works showed that elevation of cAMP levels in SC is dependent by GPR126 protein, a highly conserved orphan G protein‐coupled receptor, critical for myelination within the peripheral nervous system (PNS) during development . Interestingly, biallelic loss‐of‐function mutations in GPR126 are responsible for a lethal form of AMC (LCCS9, MIM # 616503) …”
Section: Discussionmentioning
confidence: 94%